2nd International Mobility Program: Global Project-Based Learning (gPBL) 2024 / Nor Azlan Othman, Nor Salwa Damanhuri and Norsabrina Sihab - Othman, Nor Azlan; Damanhuri, Nor Salwa; Sihab, Norsabrina (PKE, UiTMCPP, 2024)
Fostering Cross-Cultural Knowledge and Hands-On Learning in Robotics gPBL 2024 aimed at fostering cross-cultural knowledge exchange and hands-on learning in robotics. With participants from diverse nations, this program offered a vibrant platform for students to: Collaborate on engineering challenges Share expertise in innovative solutions Highlight engineering innovations within a global context